Analisis Kebijakan Pendidikan Dalam Perspektif Madrasah - Dian Hidayati; Syaeful Arif (Syntax Idea)
Madrasah has a strategic role in nation building. Currently the education of madrasa education is still considered "second class". This occurs because of the implementation of the madrasa still faces a number of major issues such as the management problems start and the low quality of madrasah education. This paper is intended to give an overview of the progress madrasah education system in Indonesia, madrasas issues, opportunities and challenges of the madrasa. Madrasah has become part of the national education system. The method used in this study is a literature study by collecting secondary data from various sources of books and journals, and then perform a descriptive analysis of the data presented in detail. Various problems encountered include management madrassa education, the gap between public and private, the quality of madrasah, to the opportunities and challenges for madrasah in Indonesia at this time.